2015
DOI: 10.1063/1.4907225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secondary emission on the argon plasma afterglow with large dust density

Abstract: A zero-dimensional, space-averaged model for argon plasma afterglow with large dust density is developed. In the model, three groups of electrons in the plasma afterglow are assumed: (i) thermal electrons with Maxwellian distribution, (ii) energetic electrons generated by metastable-metastable collisions (metastable pooling), and (iii) secondary electrons generated at collisions of ions with the electrodes, which have sufficiently large negative voltages in the afterglow. The model calculates the time-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In addition, the thermal electron density increase due to secondary electron emission is about a few percent in both dusty and dust-free plasma afterglows. However, while the simulation results of Denysenko et al [70] are in good qualitative agreement with experimental measurements, there is a quantitative discrepancy, especially in the late afterglow. It was suggested that this discrepancy might be due to a deviation of the EEDF from a Maxwellian distribution.…”
Section: Influence Of Dust On Plasma Decaymentioning
confidence: 66%
See 3 more Smart Citations
“…In addition, the thermal electron density increase due to secondary electron emission is about a few percent in both dusty and dust-free plasma afterglows. However, while the simulation results of Denysenko et al [70] are in good qualitative agreement with experimental measurements, there is a quantitative discrepancy, especially in the late afterglow. It was suggested that this discrepancy might be due to a deviation of the EEDF from a Maxwellian distribution.…”
Section: Influence Of Dust On Plasma Decaymentioning
confidence: 66%
“…They showed that the negative self-bias voltage that remains on the powered electrode during the afterglow (the self-bias voltage decays exponentially as in an RC circuit) is sufficiently large to induce secondary electrons by collisions between the positive ions and the electrode. Using a time-dependant zerodimensional, space-averaged global model taking into account thermal electrons with Maxwellian EEDF, energetic electrons generated by metastable-metastable collisions (metastable pooling), and secondary electrons generated by ion collisions with the bias electrodes, Denysenko et al [70] were able to estimate the effect of the secondary electron emission on the afterglow electron density as a function of the secondary emission yield. They reported that the effect of secondary electrons is not as large as metastable pooling in the dusty plasma afterglow, while in the dust-free afterglow, their effect might surpass metastable pooling.…”
Section: Influence Of Dust On Plasma Decaymentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the increase of the electron density in the early afterglow was attributed to the release of electrons from the dust particles by secondary electron emission in ion-dust collisions [25]. The other sources of electrons in the early afterglow were identified and compared, such as electron generation in metastablemetastable and metastable-dust collisions [22] or secondary electron emission from electrodes [26]. In a presence of impurities, such as acetylene, the metastable -acetylene collisions make a significant contribution to the described phenomenon [27].…”
Section: Introductionmentioning
confidence: 99%